COMPARISON BETWEEN PERCEIVE OF SOCIAL SUPPORT AND SELF-ACCEPTANCE AMONG MALE AND FEMALE OF DIPLOMA COLLEGE STUDENTS IN MALAYSIA - Fatinah, Nurhanis; Mohamed, Nor Firdous; Ibrahim, Shahiran (Islamic Psychology Study Program, Institut Agama Islam Negeri Syaikh Abdurrahman Siddik Bangka Belitung, 2024)
This study aimed to determine association between perceived social support and self-acceptance, with further analysis conducted to compare gender (male and female) in perceived social support and self-acceptance among polytechnic students. A cross-sectional survey was conducted with 177 students who consented to participate (90 males, 87 females), with an age range between 18 and 25 years old. The respondents were recruited using convenience sampling. Validated measures, including the Multidimensional Perceived Social Support (MPSS) and the Unconditional Self-Acceptance Questionnaire (USAQ), were employed in this study. Descriptive analysis and inferential analysis using Pearson's correlation and independent t-tests were utilized to analyze the data. The current findings suggested a non-significant relationship between perceived support from family [r (177) = - .073, p = .335] and self-acceptance. Conversely, there was a significant positive relationship between perceived support from friends and self-acceptance [r (177) = .191, p = .011], as well as between perceived support from significant others and self-acceptance [r (177) = .177, p = .019]. Furthermore, no significant differences were found between male and female polytechnic students regarding perceived social support, including family, friends, and significant others. However, a significant difference was observed in gender and self-acceptance t (175) = -3.307, p < .001) with the mean score for male self-acceptance lower than that of females. These findings contribute to the existing literature and underscore the importance of social support and self-acceptance in the well-being of diploma college students.